The effect of biodigestate and sewage sludge on the switchgrass growth, biomass elemental composition and thermal characteristics - Kharytonov, Mykola; Харитонов, Микола Миколайович; Martynova, Nadia; Мартинова, Надія; Babenko, Mykhailo; Бабенко, Михайло; Lemishko, Svitlana; Лемішко, Світлана Миколаївна; Samarska, Alla; Самарська, Алла; Gispert, Maria; Гісперт, Марія (Taylor & Francis, 2025)
Low-productive lands that are unsuitable for growing agricultural products can be successfully used to create plantations of energy crops. Depending on the dose, productivity increased by 1.7-2.6 times. In the first years, the biomass yield after adding biodigestate (BD) was 10-20% higher than in the experiment with sewage sludge (SS). The effect of sewage sludge application was longer than that of biodigestate. The content of mobile phosphorus in loess-like loam after the introduction of biodigestate in three doses exceeded the corresponding values for sewage sludge by 14-45%. At the same time the content of zinc, cobalt, nickel and lead in loess-like loam after the introduction of sewage sludge in three doses exceeded the corresponding values for biodigestate by 9-11%, and for cadmium and chromium by 31-40%. The content of trace elements, including toxic ones, in switchgrass biomass was small and did not exceed the recommended limits for plants even with the introduction of large doses of sewage sludge and biodigestate. In general, the uptake of trace elements in plots with sewage sludge was higher than in areas with biodigestate. The thermal effect of biodigestate application was more pronounced than that of sewage sludge Малопродуктивні землі, непридатні для вирощування сільськогосподарської продукції, можна успішно використовувати для створення плантацій енергетичних культур. Продуктивність зростала в 1,7-2,6 раза залежно від дози. У перші роки вихід біомаси після внесення біодигестату (БД) був на 10-20% вищим, ніж у експерименті з осадом стічних вод (ОСВ). Ефект від внесення осаду стічних вод був тривалішим, ніж від біодигестату. Вміст рухомого фосфору в лесоподібному суглинку після внесення біодигестату в трьох дозах перевищував відповідні значення для осаду стічних вод на 14-45%. Водночас вміст цинку, кобальту, нікелю та свинцю в лесоподібному суглинку після внесення осаду стічних вод у трьох дозах перевищував відповідні значення для біодигестату на 9-11%, а для кадмію та хрому на 31-40%. Вміст мікроелементів, включаючи токсичні, у біомасі проса прутоподібного був невеликим і не перевищував рекомендованих норм для рослин навіть при внесенні великих доз осаду стічних вод та біодигестату. Загалом, поглинання мікроелементів на ділянках зі осадом стічних вод було вищим, ніж на ділянках з біодигестатом. Термічний ефект внесення біодигестату був більш вираженим, ніж ефект від внесення осаду стічних вод.
Вплив біодигестату та осаду стічних вод на ріст проса прутоподібного, елементний склад біомаси та теплові характеристики
Keywords: Switchgrass; просо прутоподібне; biodigestate; біодигестат; sewage sludge; осад стічних вод; nutrients; поживні речовини; heavy metals; важкі метали; biomass thermolysis; термоліз біомаси